Монгол хэлний нэрийн хамаатуулах ёс: Nominal possessive category - А., Лхагвасүрэн (Mongolian Studies, 2023)
In this article I have attempted to suggest Mongolian nominal possessive catecory.. Mongolian nominal possessive category was determined into two study areas such as relative value and distinctive value. However, when we apply to the usage of the Mongolian nominal possessive predicament there are some very interesting and unique phenomena are observed. Therefore, this article aimed to reveal specificity effectswhile considering from different aspects of its usage and limitations or lack of bias of the previous studies. Especially, if we consider that Mongolian nominal possessive category modify only personal nouns could be a lack of bias. For example, In Mongolian nominal possessive category ‘нь’ was considered as determiner only relative clause to the third body. Ээж нь хийе. (Let mother do it.) Ээж нь хийв үү? (Did your mother have done it?) Ээж нь хийжээ. (Her mother has done it) In the above, ‘mother’ is in the three different possessive forms which can determine relative clause to the first body, also to the second body and to the third body. Likewise, I consider them as a unique feature of the Mongolian possessive category. Furthermore, in this article we aimed to propose a new theoretical idea concerning to Mongolian nominal possessive clause. Based on the study about topic clause, we are here intended to define the features of nominal possessive predicament. I have made major research focus on the Lee and Thompson’s overall view about topic and comment clause in this study. Mongolian nominal personal possessive category can be emphasize as a determiner of the topic clause. Thus, I came out to the conclusion that there is a possibility that can make rational reference in consideration of nominal possessive category.